Overseas experience in managing the civil service of the EU Member States for Ukraine: challenges and prospects - Palamarchuk, Igor; Mironenko, Vladislav (Theory and Practice of Public Administration, 2019)
This article deals with the analysis of the specificity of civil service personnel management in the EU Member States is made. The experience of civil service personnel management and the possibility of using them in the period of major reforms in Ukraine are analyzed. Special attention is paid to the modernization of the civil service and its adaptation to Ukrainian conditions, approximation to the ideal type of management with the least obstacles during the period of administrative reform. The analysis of the international experience showed that: senior civil servants and special education programs for them should be created; must developed the professional competences to ensure successful cooperation with European institutions, international partners and organizations; it is important to develop a competency approach during implementation of the new education programs for the civil servants, in particular should be determined key issues in training, such as human resource management, change management, leadership. Comprehensively analyzing the management of public service personnel inherent in both classical management and the current stage of the development of management practices abroad, it should be borne in mind that they should not be copied directly. Foreign experience should be treated carefully and carefully, taking into account the level of development of Ukrainian society, national traditions, psychology of domestic personnel. Otherwise, foreign experience can be of benefit, not harm.Today, transformation processes affect many areas of the state, but the key is reform of public administration and the role of personnel policy implementation in HRM. Personnel management is not an end in itself, but a means of raising the level of organization and functioning of public authorities. The result of effective personnel management should be high organization, clear definition of functions, establishment of hierarchies of positions, overcoming of parallelism in work, strengthening of executive discipline, regulation of official relations.